Pendidikan Islam Dalam Perspektif Pendekatan Sosiologi - Seka Andrean Habib Abdillah; Aulia Diana Devi (Al - Azkiya : Jurnal Ilmiah Pendidikan MI/SD, 2020)
Sociological is the approach of the study of education, delivering to understand the relationship of sociology with education. This study aims to find out about Islamic education in the perspective of sociological approach. The research method used is library research, then analyzed and presented the results of data findings objectively. The results showed that the sociology of education has a diverse perspective, in line with the diversity that occurs in the perspective of sociology studies in general. The importance of a sociological approach in understanding religion, because there are many religious teachings related to social problems. The amount of religious attention to this social problem further encourages religions to understand social sciences as a tool to understand their religion. The way of understanding in the approach of the sociology of religion can be easy for those of us who are still too lay because religion is derived also because of social interests. The sociological approach as an educational sociological approach consists of individual approach, social approach, and interaction approach.